Advances in understanding the role of pentraxin-3 in lung infections - Ma, Li; Li, Dongmei; Wen, Yiyang; Shi, Dongmei (Frontiers in Immunology, 2025)
Pentraxin-3 (PTX3) is a soluble pattern recognition molecule (PRM) characterized by a C-terminal pentraxin structural domain and a unique N-terminal structural domain. As a key component of the innate immune system, PTX3 can be rapidly released into the extracellular space during microbial invasion and inflammatory responses. It plays a crucial role in regulating complement activation, enhancing the ability of myeloid cells to recognize pathogens, and exerting various immune effects. PTX3 is integral to the regulation of innate immunity, inflammation, and tumor dynamics through its dual function as both a pro-inflammatory and anti-inflammatory mediator depending on the context. This role is closely linked to its diverse molecular and cellular targets. Additionally, PTX3 has been implicated in the pathogenesis of various lung diseases through its involvement in numerous physiological and pathological processes. In this paper, we summarize the complex immunological functions of PTX3 and review the multifaceted roles it plays in the development of infectious lung diseases. Our objective is to highlight the potential for clinical targeting of PTX3 as a biomarker in infectious diseases and to propose it as a viable alternative in future therapeutic strategies.